"It's a revolving door": understanding the social determinants of mental health as experienced by formerly incarcerated people - Shivani Nishar; Esteem Brumfield; Shromona Mandal; Rahul Vanjani; Jon Soske (BMC, 2023)
Abstract Background This qualitative study seeks to understand how formerly incarcerated individuals in Rhode Island conceptualize their mental health and perceive obstacles to accessing and utilizing mental health services following recent incarceration. Methods We conducted in-depth semi-structured interviews from 2021 to 2022 with 25 people who had been released from incarceration within the past five years. We identified participants using voluntary response and purposive sampling. We analyzed the data using a modified form of grounded theory developed to capitalize on insights drawn from the lived experience of research team members, including a team member with experience of incarceration, and refined initial findings with a community advisory board with lived experience of incarceration and/or mental health issues similar to the study's sample. Results Participants overwhelmingly identified social determinants of health such as housing, employment, transport, and insurance coverage as the main obstacle to both accessing and maintaining engagement with mental health care. They also reported a level of opacity in the mental health system as they attempted to navigate it with limited systems literacy and support. Participants discussed alternative strategies that they employed when they believed formal mental health failed to meet their needs. Importantly, the majority of participants perceived a lack of empathy or understanding from their providers regarding the impact of SDOH on their mental health. Conclusions Despite growing efforts to address social determinants among formerly incarcerated people, the majority of participants believed that providers neither understood nor addressed these dimensions of their lives. Participants reported two social determinants of mental health that have not yet been adequately explored in the literature: mental health systems literacy and systems opacity. We offer some strategies for how behavioral health professionals can develop stronger relationships with this population.